(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article examines modern and topical issues of physical education in comprehensive schools. The idea of solving these issues was proposed by including badminton as an extracurricular activity in the educational process. The advantages of playing badminton as a means of developing interest in sports among schoolchildren are revealed.